Influence of fuel composition on energy parameters of gas turbine plant - G. E. Marin; B. M. Osipov; P. Zunino; D. I. Mendeleev (Известия высших учебных заведений: Проблемы энергетики)
PURPUSE. This article describes the possibility of burning natural gas from different fields in a stationary power gas turbine General Electric 6FA. METHODS. Currently, gas turbine technologies are one of the most stably developing areas related to the modernization of generating equipment. At present, modernization of power plants is underway both with gas turbine units and with units in the combined-cycle power unit in the Republic of Tatarstan. The conducted studies allow us to evaluate the effect of the component composition of the fuel on the performance of a gas turbine. Comparative studies make it possible to evaluate changes in the energy characteristics of a gas turbine operating as part of a combined cycle gas turbine unit. RESULTS. The study shows that changes in the fuel composition have an impact on the energy characteristics of a gas turbine plant (efficiency, air consumption). Work with a deviation of the Wobbe index is not permissible. The deviation of the Wobbe index for the city of Zainsk is 5.29%, therefore, when installing a gas turbine it is necessary to change the setting of the fuel system. For synthesis gas, the deviation of the Wobbe index was 22.23%, the use of this fuel is unacceptable without changing the design and setting of the fuel system, since the throughput of the fuel system is not designed for a flow rate of 27.8 kg/s. The smallest values of the amount of CO2, NO, O2 in the composition of the combustion products are achieved on the fuel gas of the city of Kazan. CONCLUSION. The use of synthesis gas as the only fuel is undesirable when operating a gas turbine in a combinedcycle unit, since the calorific value of the flue gases when operating on synthesis gas is minimal and amounts to 94.3 MW, which will affect the operation of the steam turbine.